Section 30P of the Pension Funds Act: A Review, Appeal or What? - Motseotsile Clement Marumoagae (Potchefstroom Electronic Law Journal, 2023)
Section 30P of the Pension Funds Act 24 of 1956 (hereafter PFA) is an important procedural tool that allows those dissatisfied with the Pension Funds Adjudicator's determinations to apply to the High Court for such determinations to be set aside. This article discusses this section and demonstrates that neither the legislature nor the courts have provided clarity on whether what is intended by this section is an appeal, a review or a reconsideration of determinations of the Pension Funds Adjudicator. It also illustrates the confusion that has been created by the courts with the High Court referring to this procedure as sui generis and the Supreme Court of Appeal, without referring to previous High Court decisions, referring to this procedure as an appeal in the wide sense. In this article a reflection on whether these two formulations are synonymous or if there is a need to settle for only one of them will be made. Furthermore, a call for judicial reconsideration of the applicability of the Plascon-Evan Rule in section 30P applications will be made in this article.